Applying γ‐Substituted Prolines in the Foldon Peptide: Polarity Contradicts Preorganization. Issue 3 (16th December 2014) - Dietz, Dennis; Kubyshkin, Vladimir; Budisa, Nediljko
Abstract Rational choice of chemical modifications to proline residues allows the preorganization principle to be exploited for more stable assembly of the foldon domain as a tag for trimerization. With systematic knowledge of how chemical and steric variations of the ring substituents affect the relative stabilities of exo and endo puckers, the preorganization principle should then be usable in biotechnologically synthesized foldon mutants and applicable for protein tagging elsewhere.